The impact of market risks on a sample of Iraqi commercial banks - Al-Husseini, Muhammad Ghali; Nasser, Jihan Ali (Al-Ghary Journal of Economic and Administrative Sciences, 2022)
Study design: The mathematical and statistical method was used to calculate the value at risk by relying on JP. Morgan in measuring the market risk of the hypothetical trading portfolio that is exposed to foreign exchange rate risks and stock price risks, in addition to analyzing the portfolio consisting of foreign exchange and stock positions and measuring the values at risk for each position exposed to market risk to arrive at the total market risk through the (JP) model. Morgan) and then prove its impact in a sample of commercial banks. The research was conducted on a hypothetical trading portfolio that was deliberately chosen because it has the most traded stocks in the Iraqi Stock Exchange, and it consists of (the Commercial Bank of Baghdad, the Middle East Bank, the Investment Bank of Iraq, the National Bank of Iraq, the Credit Bank of Iraq, the Gulf Commercial Bank, the Commercial Bank of Iraq, Al-Mansour Investment Bank), and for a period of seven years from ((2015 to 2021)), and the results of the standard deviation of the average stock portfolio returns showed that the National Bank of Iraq is considered the highest risk (0.177) in the hypothetical trading portfolio, and the Credit Bank of Iraq is the lowest risk (0.090) according to the deviation. The standard for the portfolio, and accordingly, the value at risk was applied to both the National Bank of Iraq and the Credit Bank of Iraq. The research reached the conclusion (explaining the amount of loss achieved during a specific period of time and a certain level of confidence has become the basic rule upon which modern risk management theory is based, because it added the quality of accuracy in predicting the market risks expected to face banks because it is a new scientific philosophy and an advanced technical method in measuring the amount of exposure. Daily risk returns, which helps risk management control and evaluate market risk in a scientific and statistical manner based on scientific facts and far from guesswork and intuition.